How to frame the un-known? The odd alliance of design and “fundamental physics” in a design school - Gentes, Annie; Renon, Anne-Lyse; Bobroff, Julien (Design and Technology Education: An International Journal, 2017)
This paper analyzes the introduction of fundamental physics in design education as a pedagogical method that trains designers to create with the un-known. It studies how three workshops offered design students to work on: superconductivity in 2011, quantum physics in 2013 and light and optics in 2014. The authors observe that introducing physics in a design curriculum was thought in terms of an “a fortiori” education program that would help practitioners to come up with pertinent questions and responses even if they cannot comprehend all aspects of the problem. The authors looked at how the workshops were handled and suggest that the educational framework had five goals that correspond to a model of design: affective (how to cope with uncertainty), reflexive learning (how to cope with processes rather than contents), cognitive (how to cope with non knowledge), economic (how to cope with the industrial society of innovation), and political (how to cope with the equality of disciplines and “indiscipline”).